Concrete Structures and Structural Elements in Modern Construction Special topic volume with invited peer-reviewed papers only - Nenadálová, Šárka; Johová, Petra; Hamplová, Kateřina (Trans Tech Publications Ltd, 2024)
The special edition focuses on the important aspects of designing, researching and analyzing the load-bearing properties of concrete-based structural elements and functional structures used in modern construction and will undoubtedly be useful to civil engineers and architects. Concrete, Concrete Structure, Mechanical Properties, Flat Slab, Masonry, Facade, Hydration Heat, Crack, Concrete Reinforcement, Steel-Concrete Composite, Blast Resistance, Shear Loading, Column, Beam Materials Science, Building Materials, Construction.
Keywords: elektronické knihy; electronic books